Ora lunyu dalane mbok?: The Use of Phatic Expressions in Traditional Selling and Buying - Chusni Hadiati (Celt: A Journal of Culture, English Language Teaching & Literature, 2017)
Selling and buying as a social praxis is commonly found in daily activities. Traditional selling and buying is generally conducted in local language or dialect. Banyumas dialect or Banyumasan is a non-standard variation of Javanese language spoken along the Serayu River. Traditional selling and buying in Banyumas, consequently, is conducted in Banyumas dialect. Language plays important role in traditional selling and buying. In addition to its referential functions, phatic functions emerge from its practice. Referential functions are realized when language is used to achieve referential things such as goods and services. On the other hand, phatic functions are gained when language is used to initiate, maintain, and end a conversation. Phatic functions are very specific to traditional selling and buying which is rarely found in modern selling and buying. In modern selling and buying, seller and buyer may not be involved in a real conversation since goods exchange still occurs without any language exchange. This article proves the functions of phatic expressions in traditional selling and buying. It employs qualitative research method and conversational analysis to find the functions of phatic expressions. Based on the analysis, phatic expressions in traditional selling and buying in Banyumas dialect are mainly functioned for greeting, thanking, asking condition, showing surprise, emphasizing, and ending a conversation.